The Role of The Teacher in the Learning Process in Inclusion Schools at State 6 Takengon Junior High School, Central Aceh District - Elidar, Sasrita; Fitrah, Hariki; Sumanti, Sumanti (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
The achievement of the planned learning program cannot be separated from the teacher's role in carrying out learning activities. The aim of this research is to explore the role of teachers in the learning process at inclusive schools at the State 6 Takengon Middle School, Central Aceh Regency. The type of research is qualitative research with a descriptive approach. Data collection techniques through observation, interviews and documentation. The informants in the research were the head of the curriculum at the education office, school principals, teachers and students. Data analysis techniques use data reduction, data display and drawing conclusions. To ensure the validity of the data, triangulation techniques were used. The research results show that the role of teachers is very important in learning, (1) the role of teachers as motivators has a good impact in improving student learning achievement, (2) the role of teachers as innovators can be seen from the innovations carried out by teachers in the learning process such as using media, strategies and learning methods, (3) the role of teachers in developing students' self-confidence which is carried out in extracurricular activities.